Pengembangan Penilaian Pembelajaran Berbasis VEO di MAN 2 Probolinggo - Ainur Rofiq Sofa; Nurul Harifah; Sus shalawati; Nurul Khofifah; Wulidatul Habibah; Umi Nisa’il Karimah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to describe the development of learning assessment based on Video Enhanced Observation (VEO) at MAN 2 Probolinggo using a qualitative approach. VEO is a video-based observation technology that provides space for both teachers and students to reflect on the learning process that has taken place. This study employed a qualitative method with a case study approach. Data were collected through participatory observation, in-depth interviews, and documentation. The results show that the use of VEO encourages teachers to engage in more objective reflection on their teaching strategies and increases student engagement in the learning process. VEO also facilitates the collaborative development of teacher professionalism. VEO-based assessment can serve as a strategic alternative to foster more adaptive, reflective, and meaningful learning.